Cultural Competency in Research: A Practical Framework for Use by Researchers, Policymakers, Community Leads and Others When Working With People From Diverse Groups. - Stepanova, Evgenia; Cooper, Matthew; Robinson‐Barella, Anna; Harris, Vicki; Rance, Abbie; Husband, Andy; Wright, David; Lorencatto, Fabi; Tolley, Clare; Tovey, Wade; Wong, Geoff; Cowie, Daniel; et al. (Health Expectations, 2026)
Background: As researchers strive to conduct culturally competent and equitable research, there remains a lack of actionable guidance across the research lifecycle. Increasingly, funding bodies require evidence of such approaches, yet a clear, practical direction for effective research practice is often lacking. Aim: To develop a practical framework, grounded in Meleis' cultural competence criteria, to guide all stages of the research lifecycle. Methods: Databases PsycINFO, ERIC, PubMed, Web of Science Core Collection and Google Scholar were searched (August–October 2025) for English‐language publications applying Meleis' framework in research contexts. Narrative and thematic analysis synthesised identified applications into draft recommendations and measures across five research stages. A modified Delphi process with 31 experts (community leads, researchers, policymakers and translators) in two survey rounds and a consensus workshop was then used to refine and finalise items, producing a co‐developed framework of actionable, measurable recommendations for culturally competent research with minoritised and/or diverse groups. Results: The review identified eight studies, yielding 41 applications of Meleis' criteria. These were distilled into 29 draft recommendations and measures, which were further refined through Delphi consensus to 25 recommendations and 25 measures, offering practice‐ready guidance across research focus, recruitment, measurement, analysis and dissemination. Contextuality was rated critical in four stages, highlighting how cultural identities shape engagement. Language was strongly prioritised in focus, recruitment and measurement, with emphasis on diverse, well‐funded interpretation and transcription strategies. Empowerment and reciprocation were noted as underused but essential for legitimacy and impact, particularly in focus and dissemination. Continuous cultural humility training was endorsed, reinforcing critiques of competence as a static skill. During consensus discussions, recommendations initially framed as optional ('could') were reframed as compulsory ('should'). The final framework is available as an accessible online resource. Conclusions: Using consensus, an evidence‐based, culturally competent research framework was co‐designed; it comprised 25 recommendations that are actionable, measurable and adaptable by researchers, policymakers, community leads and others. This framework represents a crucial step towards fostering equitable and impactful research practice. Patient or Public Contribution: A patient and public involvement group of three patients from minoritised backgrounds and two health professionals met twice to review findings, refine components and provide feedback on language, accessibility and usability.